KEPEMIMPINAN DAN PENGAWASAN DALAM PERUBAHAN SUMBER DAYA MANUSIA (SDM) LEMBAGA DAKWAH - Ibnu Apriani; Cecep Castrawijaya (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study aims to examine the role of leadership and supervision in managing human resource (HR) transformation within Islamic missionary (dakwah) institutions. In an era of rapid change, especially within the digital and social context, dakwah institutions face significant challenges related to organizational adaptation, performance, and professionalism of their human resources. Using qualitative methods through literature analysis, this study identifies leadership models and supervisory strategies that support adaptive HR development aligned with the vision of Islamic propagation. The findings highlight that transformational leadership, participatory supervision, and value-based governance are key to cultivating integrity, productivity, and commitment in da’i and support staff. The study concludes that change management in dakwah HR must be systemic, visionary, and spiritually rooted.